2011
DOI: 10.1038/ajg.2011.43
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is Related to Pancreatic Fibrosis in Humans

Abstract: To our knowledge, no study in humans had studied the effect of tobacco smoking on pancreatic tissue. We have demonstrated for the first time that current cigarette smoking is associated with total PF-specifically, intralobular PF-as compared with nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 44 publications
2
35
1
Order By: Relevance
“…The increased activation of PSCs in response to smoke exposure was corroborated by previous work documenting higher levels of pancreatic fibrosis in smokers compared with never smokers. 46 The increased levels of IL-12p40 cytokine secreted by DCs matured explicitly in response to ATRA, suggesting the involvement of ATRA in smoking-mediated immune modulation. 47 …”
Section: Discussionmentioning
confidence: 98%
“…The increased activation of PSCs in response to smoke exposure was corroborated by previous work documenting higher levels of pancreatic fibrosis in smokers compared with never smokers. 46 The increased levels of IL-12p40 cytokine secreted by DCs matured explicitly in response to ATRA, suggesting the involvement of ATRA in smoking-mediated immune modulation. 47 …”
Section: Discussionmentioning
confidence: 98%
“…It is furthermore suggested that smoking increases progression of fibrosis in other organ systems, including the pancreas, kidneys, lungs and heart [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning pancreatic disease, cigarette smoking may induce fibrosis and metastasis, hallmarks of chronic pancreatitis and pancreatic adenocarcinoma, respectively [22] . Evidence suggests that protein expression is altered in pancreatic duct cells (PaDC), and such cellular changes are implicated in pancreatic cancer and chronic pancreatitis [23].…”
Section: Introductionmentioning
confidence: 99%